Profile of major pork associated zoonotic parasites from northern India: A detailed seminal study - RAVI PRATAP CHAUHAN; HIRA RAM; R PANDA; A K NEHRA; T S VINAY; RAJAT GARG; P S BANERJEE; M KARIKALAN; A K SHARMA; R K SINGH (Indian Journal of Animal Sciences, 2022)
The present study was undertaken to document the status of three major pork associated zoonotic parasites, viz. Taenia solium cysticercus, Sarcocystis suihominis and Trichinella spp., in two north Indian states (Uttar Pradesh and Uttarakhand). Masseter, diaphragm, tongue and oesophageal muscles were collected from 450 pigs (domestic: 445, wild: 05) and examined during November 2014 to October 2017. Muscle tissue samples were initially screened by visual inspection followed by the muscle compression technique for visualization of the parasites. Tissue samples were also subjected to acid-pepsin digestion for the recovery of Trichinella spp. larvae. Out of the 450 pigs examined, T. solium cysticercus was detected in 41 (9.11%) samples, whereas sarcocysts were detected in 315 (70%) samples. Nurse cell bearing Trichinella spp. larvae were recorded in the muscle tissues of a single (0.22%) wild boar and none of the muscle tissue samples from domestic pigs were positive for Trichinella spp. infection. However, the exact species of Trichinella infecting wild boar could not be established morphologically. The findings of the study are of substantial importance for understanding the maintenance and distribution of zoonotic parasites transmitted through pork consumption in the country.